Taxonomy of freshwater gobies of the genus Rhinogobius (Oxudercidae, Gobiiformes) from central Vietnam, with descriptions of two new species - Maeda, Ken; Kobayashi, Hirozumi; Iida, Midori; Tran, Hau Duc (Zootaxa, 2024)
Taxonomy of the genus Rhinogobius was investigated for the first time in Central Vietnam. Five species occurring in this region can be distinguished by shape of their head, number of pectoral-fin rays, vertebral counts, arrangements of scales and cutaneous sensory papillae, and coloration. Two species are described as new, Rhinogobius rong sp. nov. and R. nami sp. nov., and the remaining three were identified as R. taenigena, R. leavelli, and R. similis. Though the morphology of R. leavelli and R. similis differed slightly between localities, counts and measurements overlapped, and coloration was variable. This study tentatively identifies all of those populations as R. leavelli or R. similis, but further research using additional specimens from a wider geographic range is required to clear the identity of the Rhinogobius occurring in this region. Rhinogobius rong, R. similis, and R. leavelli are distributed in both Da Nang City and Thua Thien Hue Province, with the first two species occurring widely in coastal areas, and R. leavelli restricted to inland areas. On the other hand, Rhinogobius nami and R. taenigena occur only in inland areas of Da Nang City and Thua Thien Hue Province, respectively.